Approximation of Infinitely Differentiable Periodic Functions by Interpolation Trigonometric Polynomials in Integral Metric - Serdyuk, A. S. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
We obtain asymptotic equalities for the upper bounds of approximations of periodic infinitely differentiable functions by interpolation trigonometric polynomials in the metric of L 1 on the classes of convolutions.